PENGARUH E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA - Putra, M Adriansyah Dwi; Amna, Luke Suciyati (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Entrepreneurship is often considered as a possible strategy for providing job possibilities. Despite this, many people are afraid to establish their own enterprises owing to indecision. Fortunately, technological advancements, notably the e-commerce system, have proven to be quite beneficial in this area. E-commerce enables individuals to create online enterprises that are accessible to a large number of people. Furthermore, entrepreneurship necessitates the management and presentation of reliable information, notably in accounting. Putting in place an accounting information system may substantially help entrepreneurs manage numerous business operations. A research at Bandar Lampung University's Faculty of Economics and Business investigated the influence of e-commerce and accounting information systems on entrepreneurial interest. The study relied on original data gathered from a survey sent to 224 people utilizing purposive sampling. The investigation found that e-commerce had a favorable influence on individuals' interest in entrepreneurship, whereas accounting information systems had a positive effect. However, when e-commerce and accounting information systems were coupled, both had a favorable influence on entrepreneurial interest.